ANALISIS NARASI DAN VISUAL DALAM FILM "LIKE AND SHARE" MELALUI TEORI PSIKOLOGI GESTALT - Sundari Widura; Imam Akhmad (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2024)
This article examines the film "Like and Share," directed by Gina S. Noer, using Gestalt psychology principles. The research employs a qualitative approach through narrative and visual analysis. The film "Like and Share" serves as the primary data source for this study. Additional data sources include interviews with the director or screenwriter, the script, and relevant film critiques and reviews. The study found that the film "Like and Share" applies Gestalt principles, including the Principle of Wholeness (Holism), Law of Similarity, Law of Proximity, Law of Continuity, Law of Closure, Law of Figure-Ground, Law of Symmetry, and Law of Connectedness. Analysis results in the narrative aspect include the development of 1) Characters through similarity and continuity; 2) Separation of Figure and Ground in the Narrative; 3) Connectedness in the Plot. Furthermore, in the visual aspect, it utilizes 1) Application of the Law of Similarity in Visuals; Continuity in Cinematography Techniques; Use of Figure-Ground in Visual Composition.